Managing perception and expectation in healthcare sector - Ismail, Mohd.Fais; Mohd Nor, Nurul Nadiah; Selamat, Nuramalina; HusainA, Sofiah Amir; Hamsaruddin, Siti Noorfairuz; Mansor, Noor Farazeha; A. Aziz, Nurul Asyirah; Yasib, Sheery Hazmah; T.K. Muthu Koya Thangali, Thahira Bibi (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study explored the critical success factors in managing perception and expectation within the healthcare sector. In an industry where trust and satisfaction are vital, effective management of stakeholder perceptions is essential for organizational success. This study aimed to provide insights for healthcare leader to enhanced their strategies in meeting the evolved expectations of patients and stakeholders, ultimately contributed to improved healthcare outcomes and organizational resilience